The Use of Indirect Immune-fluorescence Antibody Testing (IFAT) IgM And IgG In the Diagnosis of Melioidosis - Janaki, Arumugam; Rozi, Nur Raziana Binti; Mahmud, Mohammed Imad A Mustafa; Rahman, Jamalludin Bin Ab; Rahman, Ahmad Kashfi Bin Hj Ab; Hin, How Soon (International Journal of Human and Health Sciences (IJHHS), 2021)
Introduction: Meliodosis is an important public health disease caused byBurkholderiapseudomallei. Early laboratory diagnosis is crucial for appropriate treatment due to its high mortality rate. Objective: This study is conducted to assess the potential role of the in-house IFAT IgM and IgG as the serodiagnostic tool in melioidosis and to determine the cut-off levels. Method: 40 culture-confirmed melioidosis patients were recruited. Controls consisted of a group of 40 patients without active infection and another group of 40 patients with positive blood culture for organisms other thanBurkholderiapseudomallei. Results and Discussion: Using the receiver operating characteristic (ROC) curve, the best cut-off levels determined to diagnose melioidosis are 1:20 for IgM and 1:80 for IgG. Of these cut off levels, the sensitivity and specificity for IgM are 72.5% and 80% respectively and 65% and 87.5%respectively for IgG which also has high background seropositivity. Conclusion: IFAT IgM at the cut-off level 1:20 is recommended for diagnosis. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 307-314